1991
DOI: 10.2105/ajph.81.11.1429
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic populations in public mental health: services choice and level of use.

Abstract: BACKGROUND. Barriers to access and use of mental health care by Asians, Blacks, and Hispanic Americans have been a source of concern for many years. Limitations in our knowledge base persist regarding patterns of use in public sector programs of certain services. Using a sample of almost 27,000 persons, this study examined access and level of use by ethnic minority groups of emergency services, inpatient care, individual outpatient visit, and case management. METHODS. Data from the management information syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(95 citation statements)
references
References 12 publications
7
87
1
Order By: Relevance
“…Cultural factors may also affect acceptance of and adherence to treatment plans proposed by providers (Adebimpe et al, 1982;Hu et al, 1991;Lopez, 1989). Recent studies in the physical health sector demonstrated poorer compliance among minority adults in the treatment of HIV (Mehta et al, 1997) and renal disease (Curtin et al, 1999) and among minority children in the treatment of asthma (Krishnan et al, 2001), even after adjusting for factors such as age, education, employment, access to insurance, and symptom frequency (Krishnan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural factors may also affect acceptance of and adherence to treatment plans proposed by providers (Adebimpe et al, 1982;Hu et al, 1991;Lopez, 1989). Recent studies in the physical health sector demonstrated poorer compliance among minority adults in the treatment of HIV (Mehta et al, 1997) and renal disease (Curtin et al, 1999) and among minority children in the treatment of asthma (Krishnan et al, 2001), even after adjusting for factors such as age, education, employment, access to insurance, and symptom frequency (Krishnan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Matsuoka and colleagues discovered a differential pattern of usage, with Asian Americans being three times less likely than European Americans to use mental health services for all types of services across all types of facilities (e.g., inpatient, outpatient, residential care). However, when utilization of public mental health services were examined, Asian Americans were more likely to use individual therapy and medication management and were less likely to use crisis services compared to their European American counterparts (Hu, Snowden, Jerrell, & Nguyen, 1991;Maynard, Ehreth, Cox, Peterson, & McGann, 1997). Sue, Fujino, Hu, Takeuchi, and Zane (1991) examined information on outpatient clients that were submitted by mental health agencies to the Los Angeles County Department of Mental Health during a 5-year period.…”
Section: Utilization Of and Satisfaction With The Mental Health Systemmentioning
confidence: 99%
“…Many studies have shown underutilization of specialty mental health services for psychiatric symptoms and disorders by African-Americans and Hispanics, even after controlling for levels of psychiatric pathology. [15][16][17][18][19] These minority groups are less likely to ever be in contact with specialty mental health services, and they are likely to use them less frequently once in the system. However, blacks and whites have reported discussing emotional, nervous, drug, and alcohol problems in general medical settings at similar rates.…”
mentioning
confidence: 99%